PERAN OTORITAS JASA KEUANGAN DALAM PENGAWASAN PERBANKAN UNTUK MENCEGAH TINDAK PIDANA KORUPSI DI PT. BANK SUMUT (Studi : Putusan Tipikor Pengadilan Negeri Medan No. 93/Pid.Sus-TPK/2016/PN.Mdn. Jo. Putusan Pengadilan Tinggi Medan No. 06/Pid.Sus-TPK/2017/PN - Muhammad Firdaus; Bismar Nasution; Sunarmi Sunarmi; Muhammad Ekaputra (Universitas Sumatera Utara, 2018)
ABSTRACT Cases of banking crime, not just criminal acts that occurred in the banking sector, apparently against the government banks including PT. Bank Sumut as a Regional Owned Enterprise (BUMD) of North Sumatera Province and Sub-Province / Municipality under it, incorporated as Limited Liability Company (PT) can also be investigated and investigation of alleged corruption. However, who is entitled to conduct such alleged corruption investigation in PT. Bank of North Sumatra, whether the Indonesian Police, the Attorney General, Corruption Eradication Commission, or OJK itself? Even if it is true (